The Blockade of Bank Account by the Use of Stir – Danger or Protection for Taxpayers in the Light of Sac’s Decisions - Witczak, Radosław (Journal of Finance and Financial Law, 2022)
The purpose of the article/hypothesis. The purpose of the paper is the evaluation of using STIR to blockade the bank account by tax administration. The research hypothesis is as follows: The blockade of the bank account by the use of STIR is abused by tax administration.Methodology. The descriptive study including critical attitude to legal acts and literature was used as well as the case studies of SAC’s decisions were applied as scientific methods.Results of the research. Tax frauds in VAT are an important problem of security of taxpayers. One instrument to combat them is the blockade of bank account by the use of STIR. Tax authorities very seldom use the blockade of bank account by the use of STIR. The analysis of SAC’s decisions shows that tax authorities do not abuse this instrument. The blockade of bank account by the use of STIR decreases tax frauds and increases the security of taxpayers.